A qualitative study of the perspectives of health workers and policy makers on external support provided to low-level private health facilities in a Ugandan rural district, in management of childhood infections - Juliet Mwanga-Amumpaire; Joan N. Kalyango; Karin Källander; Radhika Sundararajan; Judith Owokuhaisa; Joseph Rujumba; Celestino Obua; Tobias Alfvén; Grace Ndeezi (Taylor & Francis Group, 2021)
Background With the under-five child mortality rate of 46.4 deaths per 1000 live births, Uganda should accelerate measures to reduce child deaths to achieve the Sustainable Development Goal 3. While 60-70% of frontline health services are provided by the private sector, many low-level private health facilities (LLPHF) are unregistered, unregulated, and often miss innovative and quality improvement strategies rolled out by the Ministry of Health. LLPHF need support in order to provide quality health care. Objective To explore the perspectives of health workers and policy makers on external support given to LLPHF providing health care for children in Mbarara District, Uganda. Methods We carried out a qualitative study, in which 43 purposively selected health workers and policy makers were interviewed. The issues discussed included their views on the quantity, quality, factors determining support received and preferred modalities of support to LLPHF. We used thematic analysis, employing an inductive approach to code interview transcripts and to identify subthemes and themes. Results The support currently provided to LLPHF to manage childhood illnesses is inadequate. Health providers emphasised a need for technical capacity building, provision of policies, guidelines and critical supplies as well as adopting a more supportive supervisory approach instead of the current supervision model characterised by policing, fault finding and apportioning blame. Registration of the health facilities and regular submission of reports as well as multi-stakeholder involvement are potential strategies to improve external support. Conclusion The current support received by LLPHF is inadequate in quantity and quality. Capacity building with emphasis on training, provision of critical guidelines and supplies as well as and supportive supervision are key strategies for delivering appropriate external support to LLPHF.